Sociodemographic Determinants of Nutritional Status in Children with Sickle Cell Anaemia in Benin City Edo State, Nigeria - Odunvbun, Magdalene E.; Atimati, Anthony O.; Osueni, Gold I. (International Journal of Child Health and Nutrition, 2022)
Background: Nigeria has the highest burden of sickle cell anaemia (SCA) in Africa. Patients with SCA present with life-long complications in addition to growth failure. With comprehensive care, patients with SCA have improved survival and well-being, with some studies reporting overnutrition. This study aims to assess nutritional status and sociodemographic determinants in children with SCA. Methods: A descriptive cross-sectional study was carried out among children aged 1-16years attending the paediatric SCA clinics and their sex and age-matched controls. Anthropometric measurements were carried out to determine their nutritional status, and the data obtained were analyzed using SPSS software. The sociodemographic and relevant clinical information was obtained using a semi-structured questionnaire. Results: The majority (86%) of the children with SCA had normal height and weight, but the mean weight, weight for age z-score (WAZ), body mass index z-score (BMIZ) and height for age z-score (HAZ) were significantly lower than the HbAA controls. The mean WAZ was significantly higher in children from high socioeconomic class (SEC) and those whose mothers had tertiary education than those from lower educational statuses. Similarly, the mean HAZ was significantly higher in children from high SEC, tertiary maternal education and younger children. Conclusion: Most children with SCA have normal nutritional status despite significantly lower nutritional indicators compared to children with HbAA genotype. Higher educational status of mothers and SEC were associated with a significantly higher nutritional status among the subjects.